Ilmu Sebagai Prosedur (Metode Memperoleh Pengetahuan Ilmiah) - Maskhuroh, Lailatul (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2013)
Knowledge always develops from the beginning until now. It is appears immediately along with the process of human thinking. At fist knowledge is gained by the way of informal process of thinking, not related with existing methods. Then various changes have been done by fiures that appearafter doing organized towards knowledge that found by them. In the next development, human being makes knowledge as the result of thinking which is defiitely scientifi and is appropriate with procedure of human thinkingthat mentioned in the rules of the syllogism think. From several methods of obtaining knowledge, among of them are rasionaslime method, empiric, phenomenalism, intusionalism, and scientifi method, while elements inthe scientifi method as scientifi research among other through several procedures, such as formulation of problem, proposing a hypothesis, testing a hypothesis with empirical fact, and making a decision.Keywords : Science, Procedure, Knowledge, and Scientifi Method.